THE INFLUENCE OF AMERICAN SOCIETY IN KATE CHOPIN'S THE AWAKENING: A SOCIOLOGICAL APPROACH - ZULIANI, DANING (2007)
This research elaborates people's struggle in surviving their lives in the American society as depicted in Kate Chopin's The Awakening, based on a sociological approach. The aims of this research are to expose Kate Chopin's criticism against the domination of the men or the upper class of Creole culture in the American society and to identify relation between the structure of The Awakening and the social condition of America in the late of nineteenth century. This research belongs to qualitative research. In this method, there are two types of data sources, which are used, namely primary and secondary data sources. The primary data source and the object of this research is the novel The Awakening itself, meanwhile the secondary is any literature related with this research. The researcher collects the data from both, primary and secondary data sources in a sort of document as evidence. The research uses library research to collect the data. The collected data is analyzed by means of descriptive analysis. Having analyzed this novel, the writer draws conclusions as follows: first, a literary work involves the response of the author toward the social reality where they live. Second, Kate Chopin criticizes the condition at that time that was strongly dominated by the men or the upper class of Creole culture. Third, the sociological analysis shows the men and the upper class of the social structure in American society has dominated and exploited the women or the classes below them. Kate Chopin's criticism is her rationality to restructure the society, to struggle for the women's right, and to build her ideal society.